Studying the Gene Expressions of Bla OXA-51Like and Bla OXA-23Like in Acinetobacter baumannii - Abdullah , Rana Mujahid; Arkan Adnan Mahdi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Genotypic detection of some Antibiotics Resistant genes by using polymerase chain reaction (PCR). (20) Isolates of Acinetobacter baumannii that showed resistance to (Ceftaxim, Cefotaxim, Cefepim and Imipenim) were selected. The results showed that 20 isolates of A. baumannii possess the bla-OXA23 like gene, and that all isolates possess this gene with a percentage (100%). With molecular weight 605 bp. The current study showed that A. baumannii isolates carry 100% bla-OXA51like gene when studied with (20) isolates that are resistant to antibiotics (Imipenim Ceftazidime, Cifepime, Cifexime) that belong to this group of β-lactame with molecular weight 382 bp. Gene expression was done of the bla-OXA23like and bla-OXA51like. The results of gene expression for bla-OXA23like gene show decrease the gene expression for bla-OXA23like gene when treated by Ceftazidim, whereas the bla-OXA51 like gene, showed increasing in gene expression when treated by Ceftazidime.